When do health and well-being interventions work? Managerial commitment and context. (May 2015) - Greasley, Kay; Edwards, Paul
Health and well-being interventions are increasingly assessed as complex processes rather than randomized controlled trials. In this study the health and well-being interventions refer to voluntary actions and are not in response to any regulatory requirement. This article looks specifically at managerial commitment to these interventions and at the organizational context in which they occur. Ex-ante study predictions as to the effects of commitment in three organizations were made and then followed up. This commitment was positively associated with employee perceptions of health promotion campaigns. But broader impacts, such as commitment to the organization and a sense of autonomy, were not evident. The explanation lies in wider features of the organization of work: permanent constraints such as job design and shift systems ran against the aims of the health interventions. Relating well-intentioned interventions to such features of organizational life remains a challenge for many organizations.